2000
DOI: 10.1038/sj.bdj.4800548
|View full text |Cite
|
Sign up to set email alerts
|

A single visit, multidisciplinary approach to the management of traumatic tooth crown fracture

Abstract: An immediate restorative technique resolving the acute problem of traumatic tooth fracture with pulpal and periodontal involvement, in which the fragment(s) are re-alignable. Repositioning facilitated by a custom stent, using dentine/enamel bonding. A challenging, conservative and economically viable procedure within the compass of a single visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
1
20
0
5
Order By: Relevance
“…Similar cases were also reported by Starkey and Simonsen [4,5,6]. The success of reattachment depends on certain factors like the site of fracture, size of fractured remnants, periodontal status, pulpal involvement, maturity of the root formation, biological width invasion, occlusion, time, material used for reattachment, use of posts, and prognosis [7].…”
Section: Discussionsupporting
confidence: 62%
“…Similar cases were also reported by Starkey and Simonsen [4,5,6]. The success of reattachment depends on certain factors like the site of fracture, size of fractured remnants, periodontal status, pulpal involvement, maturity of the root formation, biological width invasion, occlusion, time, material used for reattachment, use of posts, and prognosis [7].…”
Section: Discussionsupporting
confidence: 62%
“…The use of posts increases retention and distributes stress along the root. Matrix for repositioning segments can be of great advantage where fragment alignment is problematic [7]. Tooth preparation technique would be relative to the site and amount of tooth fragment for reattachment [8].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that reattachment of fractured incisal fragments by using new generation bonding agents was effective against shear stresses and comparable with the intact teeth. The advantages of using the original tooth fragment over other materials include better color match, morphology, translucency, physiochemical characteristics, patient acceptance and economical [7]. Other treatment options available have associated limitations like multiple visits, stabilization and are less conservative in nature.…”
Section: Discussionmentioning
confidence: 99%
“…6 Dental makeover may involve restoring the esthetic and functional characteristics of anterior teeth predictably and reliably. 7 Makeover doesn't always come with complex and invasive treatments, but it can be done simply and predictably.…”
Section: Discussionmentioning
confidence: 99%